Potential Hurricane Wind Risk to US Rural and Urban Forests. Issue 4 (30th April 2021) - Cole, Jason; Nowak, David J; Greenfield, Eric J
Abstract: Hurricanes cause billions of dollars in damage annually in the United States and are projected to increase in intensity in the coming years. By exploring historical patterns of hurricanes and exposure of these hurricane-force winds across the landscape, areas of potentially high threat to future hurricane winds can be revealed. Combining potential threats from hurricane winds with forest data reveal the areas with the greatest potential threats to this important resource. Not surprisingly, most of the threats to forests occur in the Southeast, but the greatest threats to urban forests overall occur along the Northeast coast and in metropolitan centers in the Southeast. Overall, 4.6% of the nation's rural forest basal area is within zones of the highest risk from hurricane winds. Information on regional and local scale variations in hurricane risk can be used to aid policies and local forest management to improve forest health and sustainability.